Hubungan Dukungan Suami dengan Pemanfaatan Kelas Ibu Hamil - Yusmaharani Yusmaharani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine what factors are associated with the use of classes of pregnant women. The research design was cross sectional. The results showed that there were 163 mothers who did not take advantage of the class of pregnant women (77%). The results of the bivariate analysis showed P value <0.001 (OR: 10.6, C.I. 95%: 3,864-29,124), which means that there is a significant relationship between husband's support and the use of the class of pregnant women. In conclusion, there is a relationship between husband's support and the use of classes for pregnant women. Keywords: Husband's Support, Pregnant Women, Utilization